2008
DOI: 10.1172/jci32412
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-1 modulates the angiogenic and metastatic potential of human and mouse cancer cells

Abstract: Cells isolated from many types of human cancers express heparin-binding growth factors (HBGFs) that drive tumor growth, metastasis, and angiogenesis. The heparan sulfate proteoglycan glypican-1 (GPC1) is a coreceptor for HBGFs. Here we show that both cancer cell-derived and host-derived GPC1 are crucial for efficient growth, metastasis, and angiogenesis of human and mouse cancer cells. Thus downregulation of GPC1 in the human pancreatic cancer cell line PANC-1, using antisense approaches, resulted in prolonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
152
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 52 publications
(74 reference statements)
2
152
0
Order By: Relevance
“…Recently, this method has been reported as a definitive examination to identify tumor stem cells in various kinds of tumors. It is controversial which fixation is best for analysis; therefore, researchers usually use various fixations (Aikawa et al 2008;Arumugam et al 2005;Sasaki et al 2008). The present study indicated that it is important to select proper fixations and fixation methods for assessment of expression levels of proteins and RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this method has been reported as a definitive examination to identify tumor stem cells in various kinds of tumors. It is controversial which fixation is best for analysis; therefore, researchers usually use various fixations (Aikawa et al 2008;Arumugam et al 2005;Sasaki et al 2008). The present study indicated that it is important to select proper fixations and fixation methods for assessment of expression levels of proteins and RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…There are six members of the GPC family. GPC1 is involved in tumorigenesis and angiogenesis, and is frequently overexpressed in different human malignancies including pancreatic carcinoma, breast cancer and glioma (Aikawa et al, 2008;Kleeff et al, 1998;Kleeff et al, 1999;Matsuda et al, 2001;Su et al, 2006). GPC1 has been proposed to act as a co-receptor for FGF that enhances the binding of FGF to its receptor, subsequently promoting FGF-FGFR activation and signaling (Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, nerve growth factors from stromal nerve fibers bind and activate their receptors on cancer cells to promote proliferation and invasion of the cells along the neural tissue (Okada et al, 2004). Both the cancer cell-derived and the stromal cell-derived glypican-1, a co-receptor for heparin-binding growth factors, are found to be important for efficient angiogenesis and metastasis of the cancer (Aikawa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%